Comparing the Level of Commitment to In-Depth Reference and Research Support Services in Two Sets of Chinese Universities. Issue 2 (3rd April 2019) - Xi, Qingkui; Wu, Weiming; Ji, Junjie; Zhang, Zhenghui; Ni, Feng
ABSTRACT: The aim of this study is to compare the service levels of in-depth reference and research support services in Chinese university libraries. The samples in this study included three groups: 20 libraries from the top 100 Chinese universities, 20 midwest provincial university libraries in China, and 20 coastal provincial university libraries in China. The in-depth reference and research support services of these libraries were studied through online investigation, case study, and analysis. The results revealed that the reference services of the libraries from the top 100 Chinese universities rated superior to those of the provincial university libraries. The midwest provincial university libraries had fewer reference services than the coastal provincial university libraries. The reference services supplied by the agricultural university library were rated as the most useful, followed by science and technology, engineering, and medical university libraries, respectively. And, WeChat and QQ were useful tools that had Chinese characteristics.